Magnetic field activated drug delivery using thermodegradable azo-functionalised PEG-coated core–shell mesoporous silica nanoparticles. Issue 31 (16th July 2015) - Saint-Cricq, P.; Deshayes, S.; Zink, J. I.; Kasko, A. M.
Abstract : Core–shell Fe3 O4 @SiO2 mesoporous silica nanoparticles coated with a thermodegradable polymer allowed the release of a model drug through heating caused by a high frequency oscillating magnetic field. The polymer was made of poly(ethylene glycol) (PEG) functionalised with azo bonds that break with an elevation of temperature. Abstract : Core–shell Fe3 O4 @SiO2 mesoporous silica nanoparticles coated with a new thermodegradable polymer allowed the release of a model drug through heating caused by a high frequency oscillating magnetic field. The thermodegradable polymer was made of poly(ethylene glycol) (PEG) functionalised with azo bonds that break with an elevation of temperature.